Modeling The Influenced Factors of Remaining Operation Results Using Multiple Linear Regression - Widiya Astuti Alam Sur; Ines Saraswati Machfiroh; Ricky Iskandar (Universitas Bumigora, 2023)
The amount of Remaining Operation Results (ROR) obtained by Koperasi can reflect the health of its financial management. Many economic factors can affect the ROR of Koperasi itself. This study aims to determine the economic factors that significantly influence ROR based on a statistical model of multiple linear regression. The novelty of this research provides new analytical results that compare the most three influential factors based on previous research to show the factors significantly influencing the ROR. The quantitative data used the five years financial statements of Koperasi Sawit Makmur in 2017-2021 consists of 20 data on liabilities, net worth, assets, and ROR of Koperasi Sawit Makmur. The results show that asset variable as an excluded variable that does not affect the ROR of Koperasi with R2 = 0.961. Liabilities and net worth variables can explain 96.1% of ROR, with 3.9% can be explained by assets and other variables not included in the study. Liabilities have a negative and tangible effect, and net worth has a positive and partially real influence on ROR. The factor with the most dominant influence on ROR is net worth, with an influence percentage of 63.80%. The future research is expected to provide an overview of net worth and asset determinants using related statistical methods.